The Contribution of Self-Confidence to Mental Toughness Among Sport-Class Student-Athletes - Dimyati, Dimyati; Susanto, Ermawan; Purwanto, Joko (LITPAM, 2025)
Sport-class student-athletes face dual demands: maintaining academic achievement while optimizing sport performance. These demands require psychological readiness, particularly self-confidence and mental toughness. This study aimed to examine the effect of self-confidence on mental toughness and determine its contribution among sport-class students at MAN 2 Yogyakarta. A quantitative correlational design was employed with a saturated sample of 66 students from judo, taekwondo, karate, pencak silat, and football. Data were collected using self-confidence and mental toughness scales and analyzed through simple linear regression. The findings showed that self-confidence had a positive and significant effect on mental toughness, with R = 0.501, R² = 0.251, F = 21.47, and p < 0.001. Self-confidence explained 25.1% of the variance in mental toughness, while the remaining variance was influenced by other factors. The study concludes that self-confidence is an important predictor of mental toughness, although broader psychological and environmental factors should also be considered.